(untitled) (International Congress on Economics, Management and Business Studies, 2026)
This article examines the economic significance of cotton-textile clusters within the national economy, their role in increasing production efficiency, and the specific features of capital investment accounting in such clusters. The study analyzes the impact of cluster formation on the investment environment, mechanisms for managing financial flows, and approaches to improving accounting systems. Research findings demonstrate that optimizing capital investment accounting in cotton-textile clusters contributes to enhanced financial stability and long-term competitiveness.